Family violence in India : human rights, issues, actions, and International comparisons - Shirwadkar, Swati (Rawat Publications, 2009)
.Current research and factual data from all over the world have revealed different types of abuse taking place within the family, thus highlighting the necessity to address the issue of family violence. However, at the societal level, family matters are still seen as a private domain, not to be intervened with due to the culture of silence. Looking at the issue of family violence in the human rights perspective and the legal context, this volume explores the socio-cultural factors and the patriarchal prerogatives enmeshed in the process of development and globalization in India. The need for both qualitative and quantitative research is demonstrated through the contributions. This book presents cross-cultural research in order to balance the local and global perspectives - including countries such as U.S., Canada, Germany, U.K., France, and Armenia. With a human rights perspective, the papers present complexities of: intervention, different aspects of violence within the family and against special groups, contextual issues, limitations and dilemmas of ideologies, and the local barriers to intervention strategies.